Pemberian Pupuk Urea dan Pupuk Kandang Lembu Terhadap Pertumbuhan dan Produksi Tanaman Sawi Hijau (Brassica Juncea L.) - Harahap, Fitra Syawal; Sagala, Febri Khoiri (JURNAL AGROPLASMA, 2022)
The application of urea and cow manure on ultisol soil for mustard greens (Brassica Juncea L) aims to determine the treatment of cattle fertilizer on increasing leaf area, root volume and plant fresh weight. as well as the interaction of giving oxen fertilizer (t/ha) and urea fertilizer to mustard greens. This research was conducted in N4 Village with a height of 18 meters above sea level in Labuhanbatu Regency from December 2020 to March 2021. The study will be conducted with a factorial group design. The first factor is the provision of factorial Randomized Block Design (RAK) which consists of 2 factors, the first factor is Ox manure (K) which consists of 3 levels and the second factor is the provision of Urea fertilizer which consists of 2 dose levels, so that 6 treatment combinations are obtained. - 4 replicates each, resulting in 24 plots. Each plot consisted of 25 plants and 5 plants were taken as samples. Parameters observed were plant height (cm), number of leaves (strands), leaf area (cm2), root volume (ml) and plant fresh weight (g). The data obtained from the results of the study were statistically analyzed by means of variance and continued with the Duncan's New Multiple Range Test (DNMRT) at a level of 5%. The results of the study. urea dose of 100 kg/ha was able to produce an increase in leaf area, root volume and plant fresh weight. As well as the interaction of the application of ox-fertilizer (t/ha) and urea fertilizer gave a significant effect on the parameters of leaf area, root volume and plant fresh weight.